ケイコウ Xセン ブンセキ ソウチ ニヨル ガンセキ ノ テイリョウ カガク ブンセキ: (3)キドルイ ゲンソ - 瀬野, 公美子; セノ, キミコ; 石塚, 英男; イシズカ, ヒデオ; 本吉, 洋一; モトヨシ, ヨウイチ; 白石, 和行; シライシ, カズユキ; Seno, Kimiko; Ishizuka, Hideo; Motoyoshi, Yoichi; Shiraishi, Kazuyuki (2002)
P(論文) 国立極地研究所の蛍光X線分析装置, 理学電機工業製(RIX3000 : Rh/WデュアルターゲットX線管)による岩石試料中の希土類元素(La, Ce, Nd, Sm, Yb)の定量化学分析法をまとめた。測定は粉末試料と融剤(Spectroflux No. 100B : 80% LiBO_2+20% Li_2B_4O_7)の希釈率を1 : 2(重量比)のガラスビードを作成して行った。検量線の補正方法として, peak-over-back法と, 装置に組み込まれているマトリックス補正法との比較を行い, peak-over-back法の優位性を確認した。また, 同希釈率のガラスビードで主要及び微量元素の分析法も記述した。更に, 融剤(Li_2B_4O_7)を使用した希釈率1 : 5のガラスビードによる超塩基性岩類の主要元素の分析法についても報告した。 Analytical procedures for rare earth elements in rocks, namely La, Ce, Nd, Sm and Yb, are summarized. The analyses were performed by means of an X-ray fluorescence analyzer RIGAKU RIX3000 with a dual target, Rh/W, X-ray tube at the National Institute of Polar Research. Glass beads were prepared for the analyses from powder samples that were diluted two times by Spectroflux No. 100B (80% LiBO_2+20% Li_2B_4O_7). The peak-over-back method and the matrix correction method are compared with respect to accuracy, and the results show that the peak-over-back method is preferable to the matrix correction method. A procedure for major and minor element analyses in rocks using the same diluted glass beads is also reported. Furthermore, a new calibration curve method for major element analyses in ultrabasic rocks, using glass beads diluted with five times by flux (Li_2B_4O_7), is presented. departmental bulletin paper